Criminal History, Race, and Housing Type: An Experimental Audit of Housing Outcomes. (October 2022) - Leasure, Peter; Doyle, R. Caleb; Boehme, Hunter M.; Zhang, Gary
Although there are a number of experimental studies showing that private housing can be difficult to secure for those with criminal history, many issues in this area remain unexplored or underexplored. The goal of the current study was to address the following unexplored or underexplored issues: (a) the impact of various types of multiple conviction records on private housing outcomes, including one that possessed a certificate of relief; (b) racial differences in private housing outcomes; (c) the impact of housing type on private housing outcomes; and (d) the impact of a criminal record, race, and housing type interaction on private housing outcomes. This goal was achieved with the use of a field experiment (correspondence audit). Results showed several statistically and substantively significant differences among the criminal record, race, and housing type conditions. These results can be used to better inform individuals with criminal history who are seeking private housing options.